Digital Storytelling Islami: Inovasi Media Bimbingan Konseling untuk Pengembangan Kecerdasan Linguistik Siswa - Rendra Hendarsyah; Ulfah Ulfah; Muhamad Yasin; Ipan Fauzi; Imas Hayati (Ta’dib : Jurnal Pendidikan Islam, 2025)
This research addresses the low linguistic competence of elementary school students based on the Kemendikbudristek report (2023). The research objective is to develop Islamic-nuanced digital storytelling media for guidance and counseling services. The method used is Research and Development (R&D) with the ADDIE model, involving fifth-grade students of SDN Lagadar 01 through tests, interviews, and questionnaires. Expert validation results show a score of 4.64 (on a 5.00 scale), practicality of 85%, and effectiveness evidenced by a significant increase in linguistic intelligence (initial score: 62.4; final score: 83.6; p<0.001). The conclusion confirms that this media is a valid, practical, effective innovation that contributes to the integration of Islamic values in digital-based guidance and counseling services.